JUST IN TIME (JIT): SEBUAH PANDUAN MENUJU KEUNGGULAN KOMPETITIF - Andi Johan S (Pro Bisnis, 2008)
The most people think that JIT developing by Toyota Motor about 1970. This system integration product and assembly industry in Detroit by Henry Ford. Ford say that “Waste is the stock of materials in goods in excess of requirement that turns up in high prices and  low wages” (Jhonson and Wood, 1996). In 1980, industries in USA and Eropa begin to use JIT and adoption from Jepang. One people say that “zero inventory system, lean production system, synchronous manufacturing, stockless production (Hawlett-Packard), material as needed (Harley Davidson), Continuous flow manufacturing (IBM), and constraints theory (Goldratt”). Keyword : JIT, Pull System, Push System